Team-based learning in an engineering course: An experience in Brazil - Morais, Anderson A. (2019)
Team-Based Learning (TBL) is an active learning strategy, used for the first time in medical education, and its use in Engineering Education is still not well established as in health science education. This work is about an experience of use of TBL in two consecutive years (2017 and 2018) in undergraduate Engineering course in a public university in Brazil. The objectives are to describe an experience using TBL, its impact over students' performance and perception of students and teacher about this approach. Initially, students were divided into groups from 5 to 7 members. The subject of the courses was divided into 4 modules, each one of 4 weeks. Each module started with the Readiness Assurance Process - RAP (pre-class individual assignment, e.g. readings), followed by in-class Individual Readiness Assurance Test - iRAT, and Team Readiness Assurance Test - tRAT. Both tests were applied using Information Technology tools, in this case either Socrative, or Kahoot or Plickers. During classes, students performed activities designed to develop students' critical thinking skills, applying concepts learned from RAP. Moreover, the students had to perform processes of self and peer-assessment. Average scores from the RAP were statistically higher in tRAT (group tests) than in iRAT (individual tests) (t-test; p≤0.05), in both years, indicating that teamwork and peer-instruction were important to achieve a greater understanding of the subject. The perception of the students about TBL was collected by an end of class questionnaire. For 81% of the students, TBL methodology was better than teacher centred classes. Another point to be highlighted was the use of Information Technology tools for feedback, approved by 100% of the students who answered the inquiry. As suggestions for future improvements emerged the need to improve the didactic material for pre-class studies.